The Design and Demonstrative Analysis of the Gas Turbine Operation’s Simulator - Edeowede Abhulimen, Abel (Journal of Model Based Research, 2023)
The Gas Turbine operation was investigated with a view to evolving a system designed to provide a realistic imitation of the controls and operation of a Gas Turbine, used for training purposes. Operator Training Simulator has been widely adopted by many industries being a computer simulation which attempts to model a real-life plant so that it can be studied. A well trained and skilled operator is key in increasing power plant safety and productivity. Therefore, enabling quality training for operators is becoming more important as they need to handle increased load of information and duties whereas the lack of training is a major reason for inadequate performance. By changing variables in the simulator, predictions are made about the behaviour of the engine. It is a tool to virtually investigate the behaviour of the system while in operation. This work becomes indispensable because it is prohibitively expensive or simply too dangerous to allow trainees use the real equipment in a power plant. The Gas Turbine operation’s simulator is born from Object Oriented Programming, employing key programming languages. The simulator design focused on specific tasks in the operation of the Gas Turbine which include; startup, synchronization and monitoring of vital parameters like vibration, temperature, pressure, and angle of the Inlet Guide Vane. The statuses of various valves, pumps and motors as well as the Performance of actuators and the response of concatenated components are also being tracked. The simulator was found to effectively mimic a real plant life. With this simulator, trainee operators in Gas Turbine can spend time learning valuable lessons in a "safe" virtual environment yet living a lifelike experience. This will go a long way in minimizing operators’ error in GT power plants, thereby curtailing power outages and conserving power plant components.
Keywords: Gas Turbine; Power Plant; Operation; Control; Simulator